STRESS DAN KEPRIBADIAN MAHASISWA PTKIN MENGHADAPI COVID-19 - Ari Pamungkas (Jurnal Bimbingan Penyuluhan Islam, 2020)
Abstract The Covid-19 pandemic has had a significant impact on various dimensions of life including increasing stress among students. Therefore, this study aims to analyze the relationship between stress levels and the personality type of state Islamic religious college students (PTKIN). This research is a type of quantitative research. The sample in this study were 100 students of the Faculty of Ushuluddin Adab and Da'wah at IAIN Palangkaraya using purposive random sampling technique. The data in this study used 2 standardized instruments, namely the Eysenck Personality Inventory (EPI) instrument to measure extrovert-introvert personality and stress levels using the DASS-21 instrument. The conclusion of the research data analysis is that students who have a stress level during the Covid-19 pandemic are dominated by students who have an introverted personality type. This situation shows that introvert personality types are at greater risk of experiencing stress in the face of the Covid-19 pandemic compared to students with extrovert personality types.